Comparative Analysis of the Immunohistochemical Expression of the Parkin and APC proteins in Polyps and Colorectal Adenocarcinomas - Casteleins, William Augusto; Silva-Camargo, Claudia Caroline Veloso da; Agostinho, Amanda Pereira; Baldin, Rosimeri Kuhl Svoboda; Batista, Bruno Ribeiro; Nabhen, Jacqueline; Olandoski, Marcia; Noronha, Lucia de; Sotomaior, Vanessa Santos (Brazilian Journal of Oncology, 2025)
Introduction Colorectal carcinoma is the result of a series of mutations based on the adenoma-carcinoma sequence. We aimed to perform a comparative analysis of the immune expression of the parkin (PARK2 gene) and of the APC (APC gene) proteins in samples of colorectal polyps and adenocarcinomas.Materials and Methods Through a tissue microarray, we reviewed by immunohistochemistry 284 polyps from 222 patients, as well as 73 colorectal samples of adenocarcinoma. Since more than one lesion was observed in more than half of the patients with polyps, we developed a multilevel linear regression statistical model to avoid interpretation bias.Results In the univariate analysis comparing protein expression that adenocarcinomas presented a higher expression of parkin (6.19; 95% confidence interval [95%CI]: 4.43–9.95; p = < 0.001) and APC (13.5; 95%CI: 11–15.9; p < 0.001) than the polyps. Among the colorectal polyps, a positive correlation between parkin and APC expression (0.23; p < 0.001) was also found. There are no previous studies showing overexpression of such proteins in adenocarcinomas compared with neoplastic polyps.Conclusion Parkin and APC showed a similar biological behavior in tumor suppression, with a tendency towards a de novo increase in their expression as the neoplastic cell advances in the oncogenic sequence. This indicates that parkin and APC may be involved in the late mechanisms of tumor progression control in the carcinogenesis pathway.
Keywords: immunohistochemistry; adenocarcinoma; intestinal polyps; colon; rectum; adenomatous polyposis coli